Numerical and experimental performance evaluation of an Eppler 420–based horizontal-axis hydrokinetic turbine for low-velocity river applications - Ma. Leona Maye B. Pepito (Journal of Engineering Researcher and Lecturer, 2026)
Small-scale hydrokinetic turbines offer a viable solution for harnessing renewable energy from low-velocity rivers and canals, particularly in developing countries such as the Philippines, where a large portion of hydropower potential remains untapped. However, limited studies have experimentally validated the performance of airfoil-based propeller hydrokinetic turbines optimized for shallow, low-speed water streams. This study addresses this gap by designing, simulating, fabricating, and experimentally evaluating a horizontal-axis propeller hydrokinetic turbine based on the Eppler 420 airfoil. A combined Computational Fluid Dynamics (CFD) and field-testing approach was employed to optimize blade geometry, tip speed ratio, and diffuser configuration for a turbine with a swept area of 0.18 m² operating at stream velocities of 0.7–1.3 m/s. CFD results indicate that the venturi-type diffuser increased the inlet water velocity by an average of 62%, resulting in a simulated shaft power increase from 56 W for the bare turbine to 70 W for the diffuser-augmented configuration. Field experiments conducted in a local river validated these trends, achieving a maximum measured shaft power of 65 W at 1.3 m/s with a corresponding power coefficient of approximately 0.30. The close agreement between simulated and experimental results confirms the suitability of the Eppler 420 airfoil for low-velocity hydrokinetic applications and demonstrates the effectiveness of diffuser augmentation. The findings provide practical design guidance and experimental validation for efficient small-scale hydrokinetic turbine deployment in shallow inland water streams.